Pergeseran Pemikiran Tafsir di Indonesia: Sebuah Kajian Bibliografis - Cucu Surahman (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2014)
This article portrays the development of Quranic exegesis studies in contemporary Indonesia by scrutinizing various approaches used by Indonesian Islamic scholars in understanding the Qur’an. Through a bibliographical study, the author argues that there has been a shift in the study of tafsir among Islamic scholars in Indonesia, including among the advocates of the Islamic Liberal Networks (JIL). This shift can be seen in the following aspects: 1) the way Indonesians define the nature of the Qur’an essence, revelation, codification); 2) about the people who have authority to interpret the Qur’an; 3) the methodology and tools to analyze the Qur’an; 4) references, and 5) the objective of interpreting Quran. Kata kunci: Quranic hermeneutics, Indonesia, Islamic literature, tafsir methodology, JIL.